Journal Economics, business & accountancy:EFFICIENCY OF NON-LIFE INSURANCE IN INDONESIA - Zaenal Abidin (PPPM Perbanas, 2011)
It is a fact that financial institutions among Asian countries, especially Indonesia, have beendominated by commercial banks. In addition, an insurance market share is only 10 percent ofthe financial market.